1988
DOI: 10.1002/hlca.19880710120
|View full text |Cite
|
Sign up to set email alerts
|

Silicon‐Directed Nazarov Cyclizations. Part V. Substituent and heteroatom effects on the reaction

Abstract: The ability to incorporate alkyl, alkenyl, aryl, and heteroatomic groups into substrates for the silicon-directed Nuzurou cyclization and their subsequent reactions has been investigated. In general, most of the groups are compatible with the conditions for the cyclization and do not interfere even when directly attached to the divinyl ketone. The influence of substituents on the rate of the cyclization has been addressed and is consistent with a simple mechanistic picture. 0and N-Containing functions are tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In the discussion that accompanies Scheme 1, mention was made of the preference for 73 to cyclize to Z-74. We first noticed this effect during our synthesis of 82 [Equation (27)]. [45] When we added the lithioallene (±)-80 to the Weinreb amide 79, we noticed a pronounced preference (ca.…”
Section: Control Of Absolute Stereochemistrymentioning
confidence: 96%
See 1 more Smart Citation
“…In the discussion that accompanies Scheme 1, mention was made of the preference for 73 to cyclize to Z-74. We first noticed this effect during our synthesis of 82 [Equation (27)]. [45] When we added the lithioallene (±)-80 to the Weinreb amide 79, we noticed a pronounced preference (ca.…”
Section: Control Of Absolute Stereochemistrymentioning
confidence: 96%
“…Similar use of a trimethylsilyl group has been made by Denmark and by others. [26][27][28][29][30] ( 14) Placement of the directing group need not be at the β carbon atom that is destined to become part of the fivemembered ring. Kang and co-workers have shown that ferric chloride effectively catalyzes the rearrangement of keto silane 42 to the exocyclic enone 43 [Equation (15)].…”
Section: Localizing the Double Bond In The Productmentioning
confidence: 99%
“…97 The results of alkylations of ester enolates such as (126) with~-methyl and~-CH20R substituents (which have similar sterle requirements) provide additional evidence that alkylation occurs anti to the more strongly electron-releasing~-substituent (Scheme 59).97 Presumably in (126) a lone pair of electrons on oxygen facilitates electron release by the~-carbon-'Y-carbon bond. Thus, an alkylation transition state such as (127) may obtain in such cases. Alkylations of dilithium dianions of 3-benzoylaminobutanoic acid esters have also been shown to give mainly the anti 2,3-disubstituted diastereomers.…”
Section: Diastereoselective Alkylations Of Acyclic Enolates Of Carboxmentioning
confidence: 99%
“…[43][44][45][46][47][48] These compounds exhibit a variety of biological activities, [49][50][51][52][53][54] and several of them have become interesting synthetic targets. [55][56][57][58][59][60][61] The formation of this tricyclic framework reported here it therefore worthwhile to study further with the aim to develop a short synthesis of of the 4/6/5 carbocyclic framework.…”
Section: Discussionmentioning
confidence: 97%